PEMASARAN KOPI DALAM MENDUKUNG INTEGRATED FARMING SYSTEM DI ERA DIGITAL - Maharani, Ariq Dewi; Soetriono, Soetriono; Soejono, Djoko; Arum, Ayu Puspita; Zahrosa, Dimas Bastara; Rosyady, Muhammad Ghufron; Amam, Amam (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Information technology through social media can reach wider marketing. Internet/digital-based marketing can be a practical solution in marketing products. In the field of marketing management, the creation of a product marketing website for processed coffee is very necessary as a development of coffee product marketing in Lumajang Regency. The methods applied in implementing this activity are socialization, training and structured mentoring. The results of this service are training and mentoring can have a positive impact by creating a website https://sites.google.com/view/gpsemeru to promote and market ground coffee businesses.